Role of CRH in colitis and colitis-associated cancer: a combinative result of central and peripheral effects? - Zhu, Chao; Li, Shengnan (Frontiers in Endocrinology, 2024)
Corticotropin-releasing factor family peptides (CRF peptides) comprise corticotropin releasing hormone (CRH), urocortin (UCN1), UCN2 and UCN3. CRH is first isolated in the brain and later with UCNs found in many peripheral cells/tissues including the colon. CRH and UCNs function via the two types of receptors, CRF1 and CRF2, with CRH mainly acting on CRF1, UCN1 on both CRF1 &CRF2 and UCN2-3 on CRF2. Compiling evidence shows that CRH participates in inflammation and cancers via both indirect central effects related to stress response and direct peripheral influence.CRH, as a stress-response mediator, plays a significant central role in promoting the development of colitis involving colon motility, immunity and gut flora, while a few anti-colitis results of central CRH are also reported. Moreover, CRH is found to directly influence the motility and immune/inflammatory cells in the colon. Likewise, CRH is believed to be greatly related to tumorigenesis of many kinds of cancers including colon cancer via the central action during chronic stress while the peripheral effects on colitisassociated-colon cancer (CAC) are also proved. We and others observe that CRH/CRF1 plays a significant peripheral role in the development of colitis and CAC in that CRF1 deficiency dramatically suppresses the colon inflammation and CAC. However, up to date, there still exist not many relevant experimental data on this topic, and there seems to be no absolute clearcut between the central and direct peripheral effects of CRH in colitis and colon cancer. Taken together, CRH, as a critical factor in stress and immunity, may participate in colitis and CAC as a centrally active molecule; meanwhile, CRH has direct peripheral effects regulating the development of colitis and CAC, both of which will be summarized in this review.